Kajian Pengembangan Model Manajemen Pendidikan Islam Pada Sekolah PAUD di Indonesia Era Society 5.0 - Nurdiana, Nurdiana; Mujhirul Iman; Mujahid, Tamimi (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2025)
The Society 5.0 era places humans at the center (human-centered society) by utilizing advanced technologies such as Artificial Intelligence (AI), Internet of Things (IoT), big data, and robotics to solve social problems and improve quality of life. This transformation has significant implications for the world of education.. This article aims to examine the principles, challenges, and strategies for developing an education management model relevant to the Society 5.0 era. The method used is a literature review, analyzing various sources related to education management, curriculum, and technology integration. The findings indicate that an effective educational management model in this era must integrate digital technology into learning processes and administration, prioritize adaptive leadership, implement data-driven decision-making, and strengthen collaboration with the community. Challenges such as infrastructure gaps, teachers' digital skills, and resistance to change require strategies for continuous professional development and curriculum innovation. In conclusion, developing a flexible, responsive, and human-centered educational management model is key to shaping a generation that is competent, character-driven, and ready to face global challenges in the Society 5.0 era